Pengaruh Strategi Harga Terhadap Keunggulan Bersaing Di Tengah Pandemi Covid-19 (Studi Kasus Pada Toko Besi Bardesi Baja Tasikmalaya) - Lati Sari Dewi; Asep Saeful Falah (LPPM Universitas BSI, 2022)
This study uses quantitative research that aims to determine whether price has no influence on competitive advantage in the midst of the Covid-19 pandemic like the current phenomenon. This study uses a quantitative descriptive method. The number of samples in this study were 55 respondents from customers who shop at the Bardesi Iron Shop. The selection of customer criteria using random techniques and to take the number of respondents the researchers used accidental sampling technique, with the criteria of respondents who had shopped at the Bardesi iron shop. Data collection techniques by giving questionnaires to respondents, interviews and documentation. The test results show that: 1) there is an influence on the price strategy variable on competitive advantage in the midst of the Covid-19 pandemic. the effect is 0.106 or 10.6%. and greater influence than other factors. The test results were obtained from validation and reliability tests with valid and reliable statement results to be used as research measures, 2) competitive advantage occupied a very high classification with a score of 243, 3) partially there was a significant influence between price strategy and competitive advantage, although weak, is 10.6%, the partial test shows thitungt > ttable (2057 > 1.673). The significance value of t for the price variable is 2.057 and this value is greater than the probability of 0.05 (2.057 > 0.05). So in this test, Ha is accepted and Ho is rejected, this means that there is a positive and significant effect.Keywords: Marketing Strategy. pricing strategy, and Competitive Advantage